The Effects of Sambiloto Leaf Extract (Andrographis paniculata) on Blood Sugar Regulation: An In Vivo Study - Rachmat Hidayat; Lusia Hayati (Eureka Herba Indonesia, 2020)
Sambiloto (Andrographis paniculata) is one of the most common plants in Indonesia. Sambiloto contains quite varied secondary metabolites, where this plant is rich in flavonoids, alkaloids, terpenes and glycosides. This study aims to assess the effect of Sambiloto (Andrographis paniculata) leaf extract on blood sugar levels and the expression of GLUT4 protein in muscle tissue which indicates the potential of the test extract's ability to improve blood glucose intake to cells so that it can maintain blood sugar regulation. The process of extracting sambiloto is carried out by maceration in which 500 grams of simplicia are macerated with 96% ethanol for 72 hours. After 1 week of adaptation, the mice were randomly divided into the following six groups, each containing 5 animals: Normal control group, diabetes group (negative control), diabetes + metformin group (Met; 45 mg/kg), Diabetes + ES group (50 mg/kg), diabetes + ES group (100 mg/kg) and diabetes + ES group (200 mg/kg). The treatment with sambiloto extract was able to reduce blood sugar levels significantly, were at the ES 100 and 200 mg/kg BW doses it was able to reduce blood sugar levels to reach the target below 200 mg/kg BW. The dominant flavonoids in Sambiloto leaf extract are believed to be responsible for the effect of blood glucose regulation. In conclusion, Sambiloto extract affects lowering blood sugar levels in diabetes mellitus white rats by increasing glucose intake in cells and tissues.